Implementation of Caning Punishment in Nanggroe Aceh Darussalam Province in a Human Rights Approach - Muhammad Taufiki; Sonifah Albani; Kamarusdiana Kamarusdiana (Jurnal Cita Hukum, 2023)
One of regional autonomy in Indonesia is the granting of special autonomy to the Provincial Government of Nanggroe Aceh Darussalam which is regulated in Law no. 44 of 1999 concerning the administration of Aceh's privileges. Islamic criminal law in Indonesia was born in the Province of Nanggroe Aceh Darussalam. Which law is different from Indonesian criminal law in general. Currently, the law is summarized in the Aceh Qanun number 6 of 2014 concerning criminal (jinayat) law. The discussion was related to the application of caning punishment in Aceh, which has undergone various changes in its implementation procedures to date. At present there is a conflict between the Aceh Qanun regarding the Jinayat law and the new regulation issued by the Governor of Nanggroe Aceh Darussalam Province regarding the application of the caning law. What was previously carried out in the open (in the courtyard of the mosque) was moved to a closed place, namely in a penitentiary in accordance with Governor Regulation 05 of 2018 concerning the Application of the Jinayat Procedural Law Article 30. The move to the implementation venue has been in the spotlight since the discourse of this rule until the issuance of this legal product, even now, when this material is raised for a more in-depth study, it still reaps extraordinary enthusiasm.